MICROSTRUCTURAL EFFECTS OF INTRAVITREAL BEVACIZUMAB IN IDIOPATHIC CHOROIDAL NEOVASCULARISATION - Shah, Syed Nasir Ali; Kang, Qian Yan; Fan, Xiao Juan; Shahbaz, Faisal (Journal of Ayub Medical College Abbottabad, 2015)
Background: Idiopathic choroidal neovascularization (ICNV) is a unilateral ocular disease which occurs in patients younger than 50 years and accounts for approximately 17% of patients with CNV. We evaluated microstructural effects of intravitreal bevacizumab in eyes with treatment-naïve idiopathic choroidal neovascularisation. Methods: In this case series study we reviewed the treatment and follow up records of 40 symptomatic eyes having ICNV, who received an intravitreal injection of bevacizumab (1.25 mg/0.05 mL) followed by additional doses based on optical coherence tomography findings, including intraretinal fluid, subretinal fluid, or pigment epithelial detachment. We analysed the results of best-corrected visual acuity, central retinal thickness, neovessels size (thickness and diameter), and disrupted photoreceptor length at baseline and at final visit with paired t-test. Difference in best corrected visual acuity was correlated with difference in optical coherence tomography parameters by Pearson’s correlation. Results: Mean logarithm of the minimum angle of resolution best-corrected visual acuity improved from 0.60 initially to 0.24 after treatment (p=0.01). Difference in mean central retinal thickness (82.65±44.1) µm, choroidal neovessels thickness (149.58±71.1) µm, choroidal neovessels diameter (1250.8±145.1) µm, photoreceptor disruption length (2141.20±318.8) µm were all statistically significant (p=0.01). Difference in best corrected visual acuity was correlated with optical coherence tomography parameters found no statistically significant difference. Conclusion: Intravitreal bevacizumab therapy is safe and well tolerated in ICNV eyes. Restoration of photoreceptor disruption length, decrease in central retinal thickness and choroidal neovessels size has association with visual improvement in idiopathic choroidal neovascularisation. Keywords: Idiopathic choroidal neovascularization, Cirrus HD-OCT, Subretinal fluids, Photoreceptor disruption length, Choroidal neovascularization